Comparison and identification of serum metabolomic profiles in Stage B and Stage C ejection fraction preserved heart failure - Zou, Song; Zhang, Li-Wei; Wang, Ting; Wan, Yu-Hao; Chai, Ke; Wang, Si-Ming; Meng, Chen; Cai, Jian-Ping; Wang, Hua; Yang, Jie-Fu (Frontiers in Cardiovascular Medicine, 2025)
BackgroundDisturbed metabolism correlates with the progression of heart failure with preserved ejection fraction (HFpEF). However, the discrepancy in metabolism between asymptomatic (Stage B) and symptomatic (Stage C) HFpEF patients remains unclear. This study aimed to explore the metabolic differences between Stages B and C HFpEF patients and to screen metabolites to distinguish between the two groups of patients.MethodsA total of 97 Stage B and 31 Stage C HFpEF patients were included from a previous cohort, named Frailty and Comprehensive Geriatric Assessment in Hospitalized Elderly Patients (registration number: ChiCTR1800017204). Serum metabolites of the participants were identified and quantified using targeted metabolomics (Biocrates MxP® Quant 500 kit).ResultsDifferential analysis identified 208 metabolites of 19 categories, of which lipids (n = 168), amino acids (n = 7), and related metabolites (n = 18) accounted for the top three differential metabolites. In addition, the differential metabolites were significantly enriched in 15 metabolic pathways encompassing amino acid metabolism (10 pathways), lipid metabolism (two pathways), carbohydrate metabolism (one pathway), energy metabolism (one pathway), and protein translation (one pathway). Metabolite set enrichment analysis demonstrated that the differential metabolites most likely originated from muscles and were most significantly enriched in renal disease states (continuous ambulatory peritoneal dialysis and chronic renal failure). Three non-heart-specific metabolites, i.e., cystine (AUC = 0.919), stearic acid [FA (18:0), AUC = 0.913], and N-palmitoyl sphingomyelin (SM C 16:0, AUC = 0.898), displayed higher accuracy than N-terminal pro-B-type brain natriuretic peptide (AUC = 0.838) in differentiating Stage B and Stage C patients.ConclusionCompared with Stage B control, Stage C patients suffer from extensive metabolic disorders, of which lipid metabolism and amino acid metabolism are mostly significantly impaired. The alterations of metabolites are largely attributed to renal dysfunction and muscle proteolysis. Moreover, non-heart-specific metabolites display potential diagnostic value in differentiating subgroups of patients with HFpEF.